Hybrid Vehicles: An Analysis of Efficiency and Environmental Impact - Gayrat Mukhamadiev (Universitas Muhammadiyah Sidoarjo, 2023)
This study examines the advantages and disadvantages of hybrid vehicles, focusing on their capacity to mitigate harmful emissions and improve fuel efficiency. It discusses the operating principles of internal combustion engines, electric motors, inverters, and batteries used in hybrid vehicles, illustrating their key roles in improving environmental sustainability. The research analyses three power device interconnection schemes: series, mixed, and parallel, exemplified by Chevrolet Volt and Honda models respectively. The results indicate that despite high upfront costs, hybrid vehicles significantly reduce harmful emissions and fuel consumption, particularly in urban driving conditions. Furthermore, their positive environmental impact and fuel economy potentially position hybrid vehicles as future market dominants. The study highlights the importance of hybrid vehicles in mitigating climate change and calls for continued advancements and global investment in this promising technology.Highlights: Hybrid vehicles significantly reduce harmful emissions and improve fuel efficiency, particularly beneficial in urban environments. Three power device interconnection schemes (series, mixed, and parallel) dictate the operational characteristics and efficiency of hybrid vehicles. Despite the initial high investment, the long-term benefits of hybrid vehicles such as lower fuel consumption and environmental impact could make them a dominant player in the future automotive market. Keywords: Hybrid Vehicles, Internal Combustion Engine, Electric Motor, Emission Reduction, Fuel Efficiency.